Makna Konflik Peran pada Mahasiswa dengan Peran Ganda - Ervin Nurul Affrida (WAHANA, 2017)
This study aims to understand phase of conflict and purpose in students with multiple roles. The research method used qualitative method with phenomenological approach. Data collection technique are in depth interviews. Data analysis technique used Interpretative Phenomenological Analysis (IPA). Member check as stabilization techniques credibility. The result about phase of role conflict include role conflict caused by the imbalance division of time between roles. Then, role conflict caused of behavior not consistent with role purpose. Role conflicts in students with multiple roles interpreted by still work and carry out tasks with the involvement and responsibility on multiple roles followed, and taking a stand against conflict of roles, while still working on academic assignments and teaching obligations despite the tendency to experience role conflict. Based this result can be concluded that the conflicting positions on the role of a student with a dual role is interpreted differently depending on the perception of each individual. Keywords: Meaningfullness, Role Conflict, Students With Dual Role.